Ebu Hayyan El-Endülüsi’nin En-Nükat El-Hisan Ala Maani’l-Kur’an adlı eserinin edisyon kritiği cilt: 2 - İdrissa, Mahamat (My University, 2009)
of Dissertation The author of the book En-Nikati’l – Hisan Meani’l Alâ Kur’an, which we have studied, is Esir’ûd- Din, Muhammed b. Yusuf b. Ali b. Yusuf. He is more commonly known as Esir’ûd- Din, el-Ceyyanî and el- Gırnatî, which is his personal record. Ebu Hayyan was born in Gırnata in Hijree 654/ towards the end of Shawwal. (1256 with Gregorian Calender) Ebu Hayyan, who was born into a family engaged in Islamic knowledge, was raised with skills in a variety of knowledge types. He was trained by the prominent scholars of his time in fiqh, tafseer (commentary), nahw and Qur’anic recitation; afterwards he left Andalusia and came to settle down in Egypt, where he worked as a government officer in Hadeeth, Recitation, Nahw, Fiqh and Tafseer teaching and wrote over 60 books on these sciences, for which he worked as a teacher. There are also some Turkish, Persian and Habesh language books among these. We have divided the book of En-Nikati’l - Hisan Alâ Meani’l Kur’an, written by Ebu Hayyan el Endülüsi, into two parts for our study. In the first part, we have put forward the social, political and economical circumstances of Ebu Hayyan’s period. Moreover, we have provided information and insight into Ebu Hayyan’s life, knowledge and cultural studies. In the second part, we have made the edition criticism of En-Nikati’l - Hisan Alâ Meani’l Kur’an. Under the title “criticism of En-Nikati’l - Hisan Alâ Meani’l Kur’an” in our study, we have introduced the title of the book, the fact that it belongs to Ebu Hayyan (which, for sure, is ascertained, and undoubtedly the book has been written by the author), the reason why the author wrote the book, the theme of the book, the method used in writing the book, the sources of the book, the copy used in the study and finally the method used in the study, all of which has been covered separately. Even though the book En-Nikati’l - Hisan Alâ Meani’l Kur’an, which we have studied, appears to have two logs such as 1/ 41 and 2/ 41 in Köprülü Library, the second copy is inaccessible. The study of the index of the book has been made as well. TEZ

Tahkikini yapmış olduğumuz En-Nikati’l - Hisan Alâ Meani’l Kur’an adlı eserin müellifi Esir’ûd- Din, Muhammed b. Yusuf b. Ali b. Yusuf tur. Daha çok Ebu Hayyan künyesi ile yani Esir’ûd- Din, el-Ceyyanî ve el- Gırnatî diye bilinir. Ebu Hayyan, Gırnata’da H 654 / yılında Şevval ayının sonlarına doğru dünyaya gelmiştir.M 1256 İlim ile iştigal eden bir aileye mensup olan Ebu Hayyan çok yönlü olarak yetiştirilmiştir.Ebu Hayyan fıkıh, tefsir, nehiv, kraat gibi ilimlerde zamanın önde gelen alimlerinden ders almış, daha sonra Endülüs’ten ayrılarak Mısır’a gelip yerleşmiş; Mısır’da devlet görevlisi olarak hadis, kıraat, nehiv, fıkıh ve tefsir öğreticiliği yapmış ve öğreticiliğini yaptığı bu ilimler üzerinde altmıştan fazla eser ortaya koymuştur.Bunların arasında Türkçe, Farsça, Habeşçe eserler de yer alır. Ebu Hayyan el Endülüsi’nin En-Nikati’l - Hisan Alâ Meani’l Kur’an adlı eserinin üzerinde yapmış olduğumuz çalışmada eseri iki bölüme ayırdık. Birinci bölümde: Ebu Hayyan’ın yaşamış olduğu dönemin sosyal, siyasal ve iktisadi şartlarını ortaya koymuş olduk. Ayrıca Ebu Hayyan’ın hayatı, ilmi ve kültürel çalışmaları hakında bilgiler verdik. İkinci bölümde: En-Nikati’l - Hisan Alâ Meani’l Kur’an adlı eserin edisyon kritiğini yapmış olduk. Çalışmamızda En-Nikati’l - Hisan Alâ Meani’l Kur’an adlı eserin incelenmesi başlığı altında eserin adının tesbiti, Ebu Hayyan’a ait oluşu (ki bu konu kesindir eserin Ebu Hayyan’a ait olduğu konusunda hiç şüphe yoktur), eserin yazılış sebebi, eserin konusu, eserin yazımında kullanılan metod, eserin kaynakları, tahkikte kullanılan nüsha, yine tahkikte kullanılan metod ayrı ayrı ele alınarak ortaya konulmuştur. Tahkikini yapmış olduğumuz En-Nikati’l - Hisan Alâ Meani’l Kur’an adlı eserin Köprülü Kütüphanesi’nde 1/ 41 2/ 41 kayıtlarıyla iki adet nüshası görünse de ikinci kısıma ulaşılamamaktadır.Eserin indeks ve fihrist çalışmaları da ayrıca yapılmıştır.
Keywords: İslam Dini; Tefsir